Preparation, stability and in vitro evaluation of liposomes containing amodiaquine / Jacques C. Scholtz - Scholtz, Jacques Coenraad (North-West University, 2011)
Malaria is a curable disease that claims nearly one million lives each year. Problems with the treatment of malaria arise as resistance spreads and new treatment options are becoming less effective. The need for new treatments are of the utmost importance. Liposomes combined with antimalarials are a new avenue for research as liposomes can increase the efficacy of drugs against pathogens, as well as decreasing toxicity. Amodiaquine is a drug with known toxicity issues, but has proven to be effective and is, therefore, a prime candidate to be incorporated into the liposomal drug delivery system. The aim of this study was to prepare, characterize and evaluate the toxicity of the liposomes with incorporated amodiaquine. The solubility of amodiaquine was determined and liposomes formulated with, and without, amodiaquine entrapped. Accelerated stability studies (at 5 'C, 25 'C with relative humidity of 60% and 40 'C with a relative humidity of 40%) were conducted during which the size, pH, morphology and the entrapment efficacy was determined. The toxicity was determined in vitro by analysing the levels of reactive oxidative species and lipid peroxidation caused by the formulations to erythrocytes infected with P. falciparum as well as uninfected erythrocytes with flow cytometry. The solubility study of amodiaquine in different pH buffers showed that amodiaquine was more soluble at lower pH values. Solubility in solution with pH 4.5 was 36.3359 ± 0.7904mg/ml when compared to the solubility at pH 6.8, which was 15.6052 ± 1.1126 mg/ml. A buffer with a pH of 6 was used to ensure adequate solubility and acceptable compatibility with cells. Liposomes with incorporated amodiaquine were formulated with entrapment efficacies starting at 29.038 ± 2.599% and increasing to 51.914 ± 1.683%. The accelerated stability studies showed the median sizes and span values remained constant for both liposome and amodiaquine incorporated liposomes at 5 'C. The higher temperatures, i.e. 25 'C and 40 'C, displayed increases in the median size, and decreases in the span for both formulations. The conclusion can, therefore, be made that both liposome and amodiaquine incorporated liposomes are stable at lower temperatures. The entrapment efficacy increased from initial values to nearly 100% during the course of the stability study. This was attributed to amodiaquine precipitating from the solution. The pH values of the liposomes and amodiaquine incorporated liposomes remained constant for each formulation; though the amodiaquine incorporated liposomes had a lower starting pH, the formulations are both thought to be stable in terms of the pH. Toxicity studies revealed low levels of reactive oxygen species as well as low levels of lipid peroxidation for both liposome and amodiaquine incorporated liposomes, on both erythrocyte and Plasmodium infected erythrocytes. From the toxicity studies it can be concluded that liposomes and amodiaquine incorporated liposomes are not toxic to erythrocytes and infected erythrocytes. It was concluded that liposomes incorporating amodiaquine could possibly be used as a treatment option for malaria. === Thesis (M.Sc. (Pharmaceutics))--North-West University, Potchefstroom Campus, 2011.